1992
DOI: 10.1143/jjap.31.401
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Coefficient and Sensitivity of Positive and Negative Resists in the Vacuum Ultraviolet Region

Abstract: We classify super-symmetric solutions of the minimal N = 2 gauged Euclidean supergravity in four dimensions. The solutions with an anti-self-dual Maxwell field give rise to anti-self-dual Einstein metrics given in terms of solutions to the SU (∞) Toda equation and more general three-dimensional Einstein-Weyl structures. Euclidean Kastor-Traschen metrics are also characterized by the existence of a certain supercovariantly constant spinor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The quantum yield was calculated to be 0.11 ± 0.03, for 110 nm thick films ( d ), and the absorption coefficient, α, was 1.2 × 10 −5 cm −1 at 160 nm . Quantum yield varies with the wavelength of the VUV light source, and previous studies have shown that the quantum yield is 0.053 at 185 nm, 0.03 at 215−230 nm, and ∼0.92 at 254 nm …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The quantum yield was calculated to be 0.11 ± 0.03, for 110 nm thick films ( d ), and the absorption coefficient, α, was 1.2 × 10 −5 cm −1 at 160 nm . Quantum yield varies with the wavelength of the VUV light source, and previous studies have shown that the quantum yield is 0.053 at 185 nm, 0.03 at 215−230 nm, and ∼0.92 at 254 nm …”
Section: Resultsmentioning
confidence: 98%
“…PMMA strongly absorbs ultraviolet radiation at wavelengths less than 160 nm (C−C bonds in the polymer backbone) and near 180 and 210 nm (C−O π−π* and n-π* transitions in the ester moieties). The high absorption coefficient of PMMA restricts the penetration of the VUV radiation to a very shallow surface layer, around 150 nm thick for 160 nm light. Primary UV photochemical reactions in PMMA are wavelength dependent ,, and give rise to a variety of chemical reactions such as cross-linking or Norrish reactions as depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation